National Identification, Social Dominance Orientation, and Attitudes Towards Black Pete in the Netherlands: Person- and Variable-Centered Analyses - Daudi van Veen; Rosanneke A. G. Emmen; Judi Mesman (Social Psychological Bulletin, 2022)
Black Pete, a blackface figure, is a popular but controversial part of the Dutch Sinterklaas festivity. Many ethnically Dutch people do not consider the figure to be a racist phenomenon and prefer not to change the figure, although many Black people in the Netherlands consider the figure to be racist. Prior research and public discourse suggest that national identity and wanting to maintain group dominance may explain why many ethnically Dutch people do not want to change the figure. Using a person-centered approach, we investigated if subgroups could be identified whose positive attitudes towards Black Pete and Sinterklaas clustered with high national identification or social dominance orientation (SDO) among Dutch university students (N = 174). Three subgroups were identified. The high national identification group scored high on positive attitudes towards Sinterklaas, Black Pete, and national identity but low on SDO. The high SDO group scored high on positive attitudes towards Sinterklaas, Black Pete, and SDO but low on national identity. The neutral-indifferent group scored low on these variables. Additionally, using a variable-centered approach, we investigated if higher national identification and SDO would be associated with stronger positive towards Sinterklaas and Black Pete. Higher national identification, but not SDO, was associated with stronger positive attitudes towards Sinterklaas. However, national identification and SDO were both associated with stronger positive attitudes towards Black Pete. These findings suggest that many people who prefer not to change Black Pete also have identity concerns or a preference for cultural dominance.